PENGARUH MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR DI SD NEGERI 90 PALEMBANG - Nurhasanah, Nurhasanah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The purpose of this study is to determine the effect of student learning motivation on student learning outcomes State Elementary School 90 Palembang. The approach used in this research is quantitative approach, while research method is descriptive correlation. This descriptive correlational method is expected to be able to obtain a real picture of the research variables so that it can diketahuo relationship between the two variables. The population used in this study is the students of Elementary School 90 Palembang amounted to 60 people. From the results of the study showed that there is influence of learning motivation has a significant effect on student learning outcomes on the lesson. This is shown through the correlation coefficient of 0.4231 if the interprestasikan in the form of correlation coefficient table included in the category of being